2005
DOI: 10.2214/ajr.184.1.01840299
|View full text |Cite
|
Sign up to set email alerts
|

Observer Variation in MRI Evaluation of Patients Suspected of Lumbar Disk Herniation

Abstract: On average, more than 50% of interobserver variation in MRI evaluation of patients with lumbosacral radicular pain is caused by disagreement on bulging disks. Knowledge of clinical information does not influence the detection of herniations but lowers the threshold for reporting bulging disks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 12 publications
2
32
1
Order By: Relevance
“…In fact, the "bulging" category is the main reason for disagreement, 2,7 probably because radiologists use it as an escape option when in doubt. 26 Radiologists who participated in this study worked in different hospitals, did not have a fellowship, had not met previously to agree on diagnostic criteria, had not received any specific training with example case sets, did not use templates or on-line examples, and were unaware of patients' clinical features; and no effort was implemented to standardize nomenclature, apart from definitions included in the Nordic and CTF forms, as recently recommended. 22 In theory, all these features might have lowered interobserver agreement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the "bulging" category is the main reason for disagreement, 2,7 probably because radiologists use it as an escape option when in doubt. 26 Radiologists who participated in this study worked in different hospitals, did not have a fellowship, had not met previously to agree on diagnostic criteria, had not received any specific training with example case sets, did not use templates or on-line examples, and were unaware of patients' clinical features; and no effort was implemented to standardize nomenclature, apart from definitions included in the Nordic and CTF forms, as recently recommended. 22 In theory, all these features might have lowered interobserver agreement.…”
Section: Discussionmentioning
confidence: 99%
“…6,16,22,27 However, previous studies conducted in different settings consistently reported agreement in the interpretation of lumbar MR imaging to be only moderate, even though radiologists were highly trained experts, templates were used, or radiologists tried to reach consensus in previous meetings. [6][7][8]12,26,28 Moreover, the goal of this study was not to define measures to be taken to achieve the best possible interobserver agreement but to assess the reliability of the CTF nomenclature and to compare it with that of the Nordic nomenclature in conditions as close as possible to routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologist lumbar spine MRI agreement ranged from 60.8% to 94.4% 334,367,445,456,467 . Sensitivity and specificity were unrecorded.…”
Section: Comparison Of Diagnostic Thresholds Per Interventionmentioning
confidence: 99%
“…MRI lumbar examinations agreement for radiologists have documented agreement ranges from 60.8% to 94.4% 334,367,445,467 , but no Sensitivity or specificity levels were identified from the literature. Reporting radiographers Lumbar spine agreement ranged from 58.6% to 87.2% 345,367 , with sensitivity and specificity levels of 99% 345 .…”
Section: Comparison Of Diagnostic Thresholds Per Interventionmentioning
confidence: 99%
“…The most common current clinically approved standard for Low Back Pain diagnosis is the Magnetic Resonance Imaging (MRI) procedure. However, individual radiologists interpreting clinical Magnetic Resonance Imaging (MRI) studies are highly subjective with over 50% inter-observer variation [4]. This high inter-radiologist variation significantly influences therapeutic treatment, medical insurance decision makers, and judiciary personnel decisions.…”
Section: Introductionmentioning
confidence: 99%